The role of balanced scorecard in assessing the human resources performance in the economic companies (Learning and growth perspective) - Kouachi, Mourad; Rami, Kaouther (Milev Journal of Research and Studies, 2018)
This study aimes to identify the evaluation of human resources performance by using the Balanced Scorecard. he was concluded that the balanced scorecard transfers the strategic objectives into performance indicators and measures, the BSC has many indicators for the perspective of learning and growth that is interested to the intellectual abilities of human resources and their skill levels, the efficiency of information systems. Pherfos Company uses Dashboard to evaluate the performance of its human resources, and this leadership contains quantitative indicators (rate of development of human resources, turrnover of employees, rate of absences, frequency of work accidents).